Adolescent Life Skills Patterns Regarding Reproductive Health (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Adolescence is a stage of change that develops rapidly both in terms of physical, psychological, and intellectual changes that affect the attitudes and behaviors of adolescents in everyday life. Adolescence is prone to various reproductive health problems. The sophistication of technology and information that is easily accessible to adolescents is an influential factor in adolescent behavior patterns. However, this must be balanced with good knowledge, in order to direct adolescents in a positive direction. Knowledge of reproductive health is important for adolescents in adapting to changes during the transition. Adolescent independence determines attitudes in decision making that have an impact on their health status. The purpose of this study was to determine the pattern of adolescent life skills about reproductive health at SMAN 1 Godean Sleman Yogyakarta. Method: This research is a quantitative, descriptive research. The population of this study was class X students at SMAN 1 Godean Yogyakarta totaling 112 with total sampling techniques. The research instrument is an adolescent life skills questionnaire on reproductive health with 10 question indicators. Data analysis using frequency distribution. Result: The results showed that adolescents who were classified in the capable category amounted to 65 respondents (58%) and adolescents who were not capable amounted to 47 respondents (42%). Conclusions Discussion/ Suggestion: It can be concluded that most adolescents have good life skills related to reproductive health. Recommended for adolescent to actively seek health information, both physical health and mental health, so that adolescent have good life skill and are skilled decisions making.